Comprehensive Analysis of the Research Results of Wear Resistance and Physical and Mechanical Properties of Composite Polymer Materials - PhD, M.B. Mukhitdino, PhD, I. I. Akhmedov; I. I. Umarov (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article discusses the results of studies of the influence of filler content on the wear rate and physical and mechanical properties of composite polymer materials, in particular wear resistance, hardness, dynamic modulus of elasticity, tensile and impact strength, thermal conductivity and volumetric resistance of these materials working in contact interaction with concrete.